2019
DOI: 10.1101/530881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating potential drug targets through human loss-of-function genetic variation

Abstract: Human genetics has informed the clinical development of new drugs, and is beginning to influence the selection of new drug targets. Large-scale DNA sequencing studies have created a catalogue of naturally occurring genetic variants predicted to cause loss of function in human genes, which in principle should provide powerful in vivo models of human genetic "knockouts" to complement model organism knockout studies and inform drug development. Here, we consider the use of predicted loss-of-function (pLoF) variat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…In addition, we provide a precomputed file of the transcript expression value for every possible single nucleotide variant in the human genome. This metric has already proven useful in variant curation for drug target identification (32) and for filtering variants for identification of human knockouts(1). Overall, our metric can be incorporated into variant interpretation in Mendelian disease pipelines, rare variant burden analyses, and the prioritization of variants for recall-by-genotype studies.…”
Section: Figure 3: Functional Validation Of Transcript-expression Basmentioning
confidence: 99%
“…In addition, we provide a precomputed file of the transcript expression value for every possible single nucleotide variant in the human genome. This metric has already proven useful in variant curation for drug target identification (32) and for filtering variants for identification of human knockouts(1). Overall, our metric can be incorporated into variant interpretation in Mendelian disease pipelines, rare variant burden analyses, and the prioritization of variants for recall-by-genotype studies.…”
Section: Figure 3: Functional Validation Of Transcript-expression Basmentioning
confidence: 99%
“…The only established knockout phenotype is a peripheral neuropathy, apparently due to deficiency of myelin maintenance signaling to a Schwann cell receptor 14 , which is histologically evident yet phenotypically mild to undetectable in homozygotes and is not observed in heterozygotes 15,16 . Heterozygous inactivating mutations also appear to be tolerated in humans 17,18 , minimizing any concern about on-target toxicity of pharmacologic PrP lowering.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis results in a final dataset of 255 gnomAD individuals and 97 UK biobank individuals with 134 unique high-confidence pLoF variants (Figure 1a), an overall carrier frequency of 0.19%; less than half the frequency estimated from uncurated variants, reaffirming the importance of thorough curation of candidate LoF variants 31 . A subset of 25 gnomAD samples with 19 unique LRRK2 pLoF variants with DNA available were all successfully validated by Sanger sequencing ( Supplementary Table 3).…”
Section: Main Textmentioning
confidence: 78%
“…However, pLoF variants tend to be rare in human populations 29 , and are also enriched for both sequencing and annotation artefacts 30 . As such, leveraging pLoF variation in drug target assessment typically requires very large collections of genetically and phenotypically characterized individuals, combined with deep curation of the target gene and candidate variants 31 . Although previous studies of pLoF variants in LRRK2 have found no association with PD risk 32 , no study has assessed the broader phenotypic consequences of such variants.…”
Section: Main Textmentioning
confidence: 99%